Determination of carbaryl by ELISA (enzyme-linked immunosorbent assay) and HPLC with photodiode array detection - Toscano, IAS (2000)
ELISAs have been applied to pesticide residue analysis due to their high sensitivity and selectivity. However, some ELISAs performance may be affected by matrix components. In this work, ELISA for carbaryl in water samples was checked for interference by naturally occurring fulvic acids. The results suggested that the high fulvic acid concentration (greater than or equal to 30 mg L-1) and acidic pH conditions (pH 4.0) interfere with the signal detection decreasing the method sensitivity. A dilution of the samples and adjust to pH 8.0 are appropriate to minimize the matrix interferences in the ELISA method. Good correlation between ELISA and HPLC-DAD results was observed.